Motivation to move: Physical activity among urban area residences / Siti Fadhilah Abdul Hamid ... [et al.] - Abdul Hamid, Siti Fadhilah; Wan Norman, Wan Mohd Norsyam; Sariman, Mohd Hanifa; Mohd Pauzi, Muhammad Bakri (Universiti Teknologi MARA Cawangan Pahang, 2020)
Physical activity is one of the important parts of a healthy lifestyle. Everyone is encouraged to participate in some physical activities which are good for physical and mental health. For the urban community, active lifestyle has begun since they were aware of their health. As we knew, the number of places that can involve physical activities in an urban area are limited. Therefore, in order to do any physical activity individuals need to have a motivation in themselves to perform the physical activity. This study is designed to identify the motivation factor in performing physical activity in urban areas. The Physical Activity and Leisure Motivation Scale (PALMS) were used in this study. A total of 150 people (N= 150) from Bandar Utama Selangor that represents urban areas were selected through convenience sampling. The result of this study showed that the highest-ranking of the motivation factor level was a physical condition (M= 4.55, SD= 0.468) whereas the lowest was Others expectation (M= 2.54, SD=0.933). In conclusion, urban society involved in physical activity because of their intrinsic motivation, their self.